2015
DOI: 10.2136/sssaj2014.08.0328
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Nitrogen Supply of Rice Is Predicted by Soil Organic Carbon

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…For instance, Cui et al [17] estimated that soil N supply was increased by 5.37 kg/ha for each g/kg SOM during summer maize season and by 3.68 and 9.76 kg/ha during winter wheat season for low and high yielding fields, respectively, in the North China plain. Espe et al [18] estimated a linear effect of 1.44 kg/ha for every g/kg increase in SOC for rice on organic soils. However, Cassman et al [30] observed a poor correlation between indigenous N supply and SOC in the rice systems, and attributed the N content to the N inputs from sources other than SOM mineralization, degree of congruence between soil N supply and crop demand, and differences in SOM quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Cui et al [17] estimated that soil N supply was increased by 5.37 kg/ha for each g/kg SOM during summer maize season and by 3.68 and 9.76 kg/ha during winter wheat season for low and high yielding fields, respectively, in the North China plain. Espe et al [18] estimated a linear effect of 1.44 kg/ha for every g/kg increase in SOC for rice on organic soils. However, Cassman et al [30] observed a poor correlation between indigenous N supply and SOC in the rice systems, and attributed the N content to the N inputs from sources other than SOM mineralization, degree of congruence between soil N supply and crop demand, and differences in SOM quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cassman et al [30] observed a poor correlation between indigenous N supply and SOC in the rice systems, and attributed the N content to the N inputs from sources other than SOM mineralization, degree of congruence between soil N supply and crop demand, and differences in SOM quality. Obviously, the N supply from SOM mineralization would vary substantially, and it should be incorporated into other fertilization recommendation strategies such as site-specific nutrient management in a given region having similar soil properties, climate, and crop management [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was embedded in an N rate trial across a gradient of SOC (Espe et al, 2015). Three sites with contrasting SOC (6, 11, and 23%) were selected for this study with the distance between each site less than 1.25 km.…”
Section: Experimental Design and Field Setupmentioning
confidence: 99%
“…Only two rates (0 and 80 kg N ha À1 ) were chosen for this study. The 80 kg N ha À1 was chosen as it was the highest recommended N rate for rice production in this range of SOC contents (Espe et al, 2015). All sites were managed the same throughout the entire season.…”
Section: Experimental Design and Field Setupmentioning
confidence: 99%